Optimasi Pengendapan Albumin dengan Variasi Suhu, pH dan Konsentrasi Etanol dalam Plasma Darah melalui Metode Simplex Lattice Design - Trisna Yuliana; Sandi Adityawarman; Agus Setiyawan (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2019)
Albumin is used to treat hypoalbumimenia in various diseases. The utilization of albumin raw materials from donor blood that has exceeded the time limit of use could be advantages, which are reducing dependence on imported albumin and could reduce the cost of processing waste blood. The purity and resulting of albumin can be influenced by various parameters including; temperature, pH and ethanol concentration. In this research, the optimization process is conduct using the Simplex Lattice Design method in order to obtain an optimal composition variation of 7 (seven) parameters variation composition to obtain albumin with a high concentration. Albumin is separated by ethanol fractionation method through differences in protein solubility in plasma. Based on Anova test, the 7 (seven) composition variations of the parameters showed significant differences with p = 0.0282 (<0.05) and F test > F table. The evaluation results show that the composition of the 5th composition formula shows the optimal albumin response with temperature parameters -10oC, pH 4.8 and ethanol concentration of 40%. The albumin content obtained with the composition is 53.59 ug. Keywords: Albumin, temperature, pH, ethanol and Simplex Lattice Design